A method for preparing a spindle-shaped carbon-coated lithium iron phosphate positive electrode material

The in-situ synthesis of a carbon-coated lithium iron phosphate material using a Fe-MOF precursor addresses the inefficiencies of existing methods by enhancing conductivity and diffusivity without additional carbon sources, resulting in a stable, structured material with improved electrochemical properties.

CN115275148BActive Publication Date: 2025-01-03JIANGSU RONGHUI GENERAL LITHIUM IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210960212.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-11
Publication Date
2025-01-03
Estimated Expiration
2042-08-11

AI Technical Summary

Technical Problem

Existing methods for preparing carbon-coated lithium iron phosphate materials are cumbersome, energy-intensive, and require additional carbon sources, which hinder the improvement of electronic conductivity and lithium ion diffusivity.

Method used

An in-situ synthesis method involving the formation of a Fe-MOF precursor, followed by mixing with lithium and phosphorus sources and sintering under inert conditions to generate lithium iron phosphate, where the organic ligand is partially carbonized to form a carbon matrix, eliminating the need for additional carbon sources and simplifying the process.

Benefits of technology

The method results in a carbon-coated lithium iron phosphate material with enhanced electronic conductivity and lithium ion diffusivity, maintaining the spindle-shaped structure and providing a stable composite with improved electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115275148B_ABST
    Figure CN115275148B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a carbon-coated lithium iron phosphate positive electrode material with a spindle-shaped structure, comprising the following steps: Step 1) preparing a Fe-MOF precursor: adding an iron salt and an organic ligand to a solvent to dissolve them respectively to prepare a solution. The two solutions are mixed, stirred and mixed, and then transferred to a round-bottom flask or a reactor, heated and stirred, and a Fe-MOF precursor with a spindle-shaped structure is formed after the reaction, and the product is washed and dried; Step 2) the Fe-MOF precursor is ball-milled or ground and mixed with a lithium source and a phosphorus source, and then the mixture is moved into a tubular furnace and sintered at high temperature under an inert atmosphere; under high temperature conditions, the iron ions in the Fe-MOF react with the added lithium source and phosphorus source to form lithium iron phosphate; the organic ligand is partially carbonized and coated with the lithium iron phosphate. The present invention does not require the addition of an additional carbon source, the Fe-MOF precursor itself is the carbon source, and the molding is sintered once, the process is simple, and it is easy to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion battery positive electrode materials, and in particular to a method for preparing a spindle-shaped carbon-coated lithium iron phosphate positive electrode material. Background Art

[0002] With the growing demand for efficient energy storage facilities, lithium-ion batteries (LIBs) are widely used due to their high energy density and ultra-long cycle life, and cathode materials are an indispensable prerequisite for the development of high-performance LIBs. Among the mainstream commercial cathode candidate materials, olivine-type lithium iron phosphate (LiFePO4) is known for its high theoretical specific capacity, low price, excellent safety performance and thermal stability. However, its inherent poor electronic conductivity and lithium ion diffusivity seriously hinder its practical application in lithium-ion batteries.

[0003] CN112599730A discloses a method for preparing a carbon-coated lithium iron phosphate positive electrode material, comprising the following steps: S1, mixing a lithium source, an iron source and a phosphorus source in a lithium: iron: phosphorus molar ratio of 1:1:1 to obtain a mixture, then adding the mixture into water, performing a wet ball milling to obtain a slurry, and drying and calcining the obtained slurry to obtain a lithium iron phosphate semi-finished product; S2, placing the lithium iron phosphate precursor obtained in step S1 in a mixed solution of a carbon source and an organic solvent, and rapidly stirring; S3, ball milling the dispersion formed in step S2 to uniformly mix the raw materials; S4, calcining the material obtained in step S3 at high temperature in a mixed atmosphere of nitrogen and argon; S5, cooling the material calcined in step S4 in a mixed atmosphere of nitrogen and argon to obtain a carbon-coated lithium iron phosphate positive electrode material. It requires an additional carbon source, two ball millings, and two calcinations, and the process is cumbersome and energy-intensive. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a preparation method of in-situ synthesized carbon-coated lithium iron phosphate material which can improve the electronic conductivity and lithium ion diffusion of the material and does not require additional carbon source and iron source.

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a carbon-coated lithium iron phosphate positive electrode material with a spindle-shaped structure, comprising the following steps:

[0006] Step 1) preparing Fe-MOF precursor: mixing the iron salt solution and the organic ligand solution, stirring and mixing, then transferring to a round-bottom flask or a reactor, heating and stirring, and forming a Fe-MOF precursor with a spindle-shaped structure after reaction, and washing and drying the Fe-MOF precursor;

[0007] Step 2) The Fe-MOF precursor is ball-milled or ground with a lithium source and a phosphorus source, and then the mixture is transferred into a tube furnace and sintered at high temperature under an inert atmosphere; under high temperature conditions, the iron ions in the Fe-MOF react with the added lithium source and phosphorus source to generate lithium iron phosphate, and the organic ligand is partially carbonized to coat the lithium iron phosphate. The reaction formula is as follows:

[0008] Li + + Fe 2+ + PO4 3- = LiFePO4.

[0009] Furthermore, the iron salt in step 1) is any one or more of ferric chloride, ferric nitrate or ferric sulfate, which effectively provides iron ions. The organic ligand is any one or more of carboxylic acid, nitrogen-containing heterocyclic or nitrogen-containing oxygen mixed ligand, which effectively provides organic ligands and finally coordinates with iron ions to form Fe-MOF.

[0010] Furthermore, in step 1), the solvent of the iron salt solution and the organic ligand solution is one or more of ethanol, methanol, deionized water and N, N-dimethylformamide. The heating temperature is 50-150 °C to accelerate the reaction rate. The stirring speed is 150-300 rpm to make the reaction uniform. The reaction time is 10-20 h, which is conducive to the successful synthesis of Fe-MOF. The drying temperature is 80-150 °C and the time is 5-10 h to quickly dry the sample.

[0011] Further, the lithium source in step 2) is one or more of lithium carbonate, lithium hydroxide and lithium oxalate. The phosphorus source is one or both of diammonium hydrogen phosphate and diammonium dihydrogen phosphate. The ball milling time is 5-10 min, the rotation speed is 500-800 rpm, and if grinding, the time is 30-50 min.

[0012] Furthermore, the inert atmosphere in step 2) is one or more of nitrogen, argon, and argon-hydrogen mixed gas. The sintering conditions are: a heating rate of 1-4.5°C / min, a sintering temperature of 610-700°C, and a holding time of 6-10 hours, which is conducive to the synthesis of pure phase lithium iron phosphate materials retaining the Fe-MOF morphology.

[0013] A carbon-coated lithium iron phosphate positive electrode material with a spindle-shaped structure is prepared according to a method for preparing a carbon-coated lithium iron phosphate positive electrode material with a spindle-shaped structure.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. The present invention adds iron salt and organic ligand to a solvent to dissolve and prepare a solution. The two solutions are mixed, stirred and mixed, and then transferred to a round-bottom flask or reactor, heated and stirred, and a Fe-MOF precursor with a spindle-shaped structure is formed after the reaction. The Fe-MOF precursor is ball-milled or ground with a lithium source and a phosphorus source to mix, and then the mixture is moved into a tubular furnace and sintered at high temperature under an inert atmosphere; under high temperature conditions, the iron ions in the Fe-MOF react with the added lithium source and phosphorus source to form lithium iron phosphate; the organic ligand is partially carbonized and coated with the lithium iron phosphate. The present invention does not require the addition of an additional carbon source, the Fe-MOF precursor itself is the carbon source, and the formation is performed by sintering at one time, the process is simple, and it is easy to operate.

[0016] 2. The present invention derives the carbon matrix from the organic ligand part in Fe-MOF by calcination in an inert atmosphere under high temperature and oxygen-free conditions. The carbon matrix can well maintain the morphology of the Fe-MOF precursor, and its multiple pores and large specific surface area are conducive to the penetration of the electrolyte. The large number of reactive active sites enables the formed lithium iron phosphate particles to be more fully in contact with the electrolyte. At the same time, the Fe-MOF-derived carbon matrix acts as an electronic conduction buffer, effectively promoting the generation of small-sized lithium iron phosphate subunits and making them evenly distributed in the porous carbon matrix, greatly improving the electronic conductivity and lithium ion diffusivity of the material.

[0017] 3. The carbon matrix is ​​coated with lithium iron phosphate. Such a composite material has a stable structure, which ensures the cycle stability of the lithium iron phosphate material during the electrochemical reaction process. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is an X-ray diffraction analysis (XRD) diagram of the carbon-coated lithium iron phosphate positive electrode material prepared in an embodiment of the present invention.

[0019] Figure 2 This is a scanning electron microscope (SEM) image of the Fe-MOF and carbon-coated lithium iron phosphate positive electrode materials prepared in the present invention. DETAILED DESCRIPTION

[0020] In order to deepen the understanding of the present invention, the specific implementation mode of the present invention is described in detail below with reference to the accompanying drawings. This embodiment is only used to explain the present invention and does not constitute a limitation on the protection scope of the present invention.

[0021] Example 1

[0022] Synthesis of Fe-MOF: 0.05 mol of ferric chloride hexahydrate and 0.05 mol of sodium fumarate were dissolved in 100 mL of deionized water. The ferric chloride hexahydrate aqueous solution was first transferred to a round-bottom flask, heated and stirred to 60 °C, and then the sodium fumarate aqueous solution was added to the above solution. After stirring at 150 rpm for 15 hours at 60 °C, a reddish-brown suspension was obtained. The product was centrifuged and washed, and vacuum dried at 80 °C for 10 hours to obtain a reddish-brown powder.

[0023] Lithium carbonate, Fe-MOF and ammonium dihydrogen phosphate were weighed in a molar ratio of 3:2:6, added to an agate mortar, ground for 40 minutes, and then moved into a tube furnace. In a nitrogen atmosphere, the temperature was raised from room temperature to 700 °C at a rate of 1 °C / min, kept for 6 hours, and naturally cooled to room temperature to obtain a carbon-coated lithium iron phosphate cathode material. The prepared carbon-coated lithium iron phosphate cathode material retains the spindle-shaped structure of the precursor Fe-MOF, and the surface shows a particle aggregation.

[0024] Example 2

[0025] The synthesis of Fe-MOF was the same as in Example 1.

[0026] Lithium carbonate, Fe-MOF and ammonium dihydrogen phosphate were weighed in a molar ratio of 3:2:6, added to an agate mortar, ground for 45 minutes, and then moved into a tube furnace. In a nitrogen atmosphere, the temperature was raised from room temperature to 650 °C at a rate of 1 °C / min, kept for 8 hours, and naturally cooled to room temperature to obtain a carbon-coated lithium iron phosphate cathode material. The prepared carbon-coated lithium iron phosphate cathode material retains an overall spindle-shaped structure.

[0027] Example 3

[0028] The synthesis of Fe-MOF was the same as in Example 1.

[0029] Lithium carbonate, Fe-MOF and ammonium dihydrogen phosphate were weighed in a molar ratio of 3:2:6, added to an agate mortar, ground for 50 minutes, and then moved into a tube furnace. In a nitrogen atmosphere, the temperature was raised from room temperature to 600 °C at a rate of 1 °C / min, kept for 10 hours, and naturally cooled to room temperature to obtain a carbon-coated lithium iron phosphate cathode material. The prepared carbon-coated lithium iron phosphate cathode material exhibits a spindle-shaped structure with a relatively complete structure and a smooth surface.

[0030] Comparative Example 4

[0031] The synthesis of Fe-MOF was the same as in Example 1.

[0032] Lithium carbonate, Fe-MOF and ammonium dihydrogen phosphate were weighed in a molar ratio of 3:2:6, added to an agate mortar, ground for 40 minutes, and then moved into a tube furnace. In a nitrogen atmosphere, the temperature was raised from room temperature to 700 °C at a rate of 5 °C / min, kept for 10 hours, and naturally cooled to room temperature to obtain a carbon-coated lithium iron phosphate cathode material. Due to the fast heating rate and high reaction temperature, the structure of the prepared carbon-coated lithium iron phosphate cathode material collapsed and the spindle-shaped structure could not be retained.

[0033] Comparative Example 5

[0034] The synthesis of Fe-MOF was the same as in Example 1.

[0035] Lithium carbonate, Fe-MOF and ammonium dihydrogen phosphate were weighed in a molar ratio of 3:2:6, added to an agate mortar, ground for 40 minutes, and then moved into a tubular furnace. In a nitrogen atmosphere, the temperature was raised from room temperature to 650 °C at a rate of 5 °C / min, kept for 8 hours, and naturally cooled to room temperature to obtain a carbon-coated lithium iron phosphate cathode material. The prepared carbon-coated lithium iron phosphate cathode material has no impurities, but the heating rate is fast, and some of the material structures collapse, and the spindle-shaped structure is not retained.

[0036] Comparative Example 6

[0037] The synthesis of Fe-MOF was the same as in Example 1.

[0038] Lithium carbonate, Fe-MOF and ammonium dihydrogen phosphate were weighed in a molar ratio of 3:2:6, added to an agate mortar, ground for 40 minutes, and then moved into a tube furnace. In a nitrogen atmosphere, the temperature was raised from room temperature to 600 °C at a rate of 3 °C / min, kept for 6 hours, and naturally cooled to room temperature to obtain a carbon-coated lithium iron phosphate cathode material. The prepared carbon-coated lithium iron phosphate cathode material retains a spindle-shaped structure, but the reaction temperature is low, the time is short, and there are iron phosphate and lithium pyrophosphate impurities.

[0039] like Figure 1 It can be seen that the carbon-coated lithium iron phosphate cathode material presents an ordered orthorhombic structure, and its corresponding diffraction peak is consistent with the standard card of LiFePO4. Sintering at 650 ℃ and 700 ℃ obtains pure phase LiFePO4, while the carbon-coated lithium iron phosphate cathode material sintered at 600 ℃ may contain a small amount of iron phosphate and lithium tetrapyrophosphate impurities due to the low temperature and incomplete reaction. In addition, no obvious carbon peak was observed in the sample, indicating that the carbon matrix in the material is amorphous.

[0040] like Figure 2From the SEM image, it can be seen that the synthesized Fe-MOF precursor presents a spindle-shaped structure with a size of about 150nm×1um. In addition, the carbon-coated lithium iron phosphate positive electrode materials prepared in Examples 1, 2, and 3 all retain the spindle-shaped structure of the precursor.

[0041] The above description is a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, and these should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a spindle-shaped carbon-coated lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: Step 1) preparing Fe-MOF precursor: mixing the iron salt solution and the organic ligand solution, stirring and mixing, then transferring to a round-bottom flask or a reactor, heating and stirring, and forming a Fe-MOF precursor with a spindle-shaped structure after reaction, and washing and drying the Fe-MOF precursor; Step 2) The Fe-MOF precursor is ball-milled or ground with a lithium source and a phosphorus source, and the mixture is transferred into a tube furnace for high-temperature sintering under an inert atmosphere; the sintering conditions are: a heating rate of 1 to 4.5°C / min, a sintering temperature of 610 to 700°C, and a holding time of 6 to 10 hours; under high temperature conditions, the iron ions in the Fe-MOF react with the added lithium source and phosphorus source to generate lithium iron phosphate, and the organic ligand is partially carbonized to coat the lithium iron phosphate. The reaction production formula is as follows: Lee + + Fe 2+ + PO4 3- = LiFePO4.

2. The method for preparing a spindle-shaped carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1), the iron salt is any one or more of ferric chloride, ferric nitrate or ferric sulfate; the organic ligand is any one or more of carboxylic acid, nitrogen-containing heterocyclic or nitrogen-oxygen mixed ligand.

3. The method for preparing a spindle-shaped carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The solvent of the iron salt solution and the organic ligand solution in step 1) is one or more of ethanol, methanol, deionized water and N, N-dimethylformamide; the heating temperature is 50-150 ° C, the stirring speed is 150-300 rpm, and the reaction time is 10-20 h; the drying temperature is 80-150 ° C, and the time is 5-10 h.

4. The method for preparing a spindle-shaped carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 2), the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium oxalate; the phosphorus source is one or both of diammonium hydrogen phosphate and ammonium dihydrogen phosphate; the ball milling time is 5-10 min, the rotation speed is 500-800 rpm, and if grinding, the time is 30-50 min.

5. The method for preparing a spindle-shaped carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The inert atmosphere in step 2) is one or more of nitrogen, argon, and argon-hydrogen mixed gas. 6 . A carbon-coated lithium iron phosphate positive electrode material with a spindle-shaped structure obtained by the preparation method according to claim 1 .

Citation Information

Patent Citations

  • Preparation method of carbon-coated lithium iron phosphate positive electrode material

    CN112599730A

  • Preparation method of positive material carbon-coated LiFePO4 of lithium ion secondary cell

    CN102593461A

  • Composite lithium battery cathode material and preparation method thereof as well as lithium battery cathode and lithium battery

    CN107394139A